“Friendship” in an Orkut Community - Carvalho, Woodson Fiorini de (Estudos Semióticos, 2010)
This paper analyzes one of the many Orkut communities - “Solteiros BH” (which aims at promoting encounters and friendship), in order to assess the discursive conﬁgurations the passion Friendship acquires in virtual environments. These conﬁgurations produce an eﬀect we call “intimacy”, i.e., an eﬀect through which the addresser/narrator shows he is intimate with his addressee/narratee and becomes someone who gets privileged access to others in the group. The expression of intimacy, labelled friendship, can occur in several ways, depending on the social group in which that collective friendship is established. Therefore, we intend to investigate how those virtually established communities will negotiate the “friendship” content. The expression of friendship on Orkut is essentially produced on a written basis and adorned by photos and graphics that compose the message. Orkut-based friendship is set through pre-determined and pre-framed graphics, allowing the user to paste such items on the screen according to a compositional scheme already pre-customized by the graphic environment of the program. Its content is, thus, governed by a pre-distributed spatiality and subject to a recipe of “how to make friends”, in the euphoric certainty that friendship will inexorably happen through this mechanism. This article is the result of a pilot study that investigated a text that opens one of those virtual communities, assessing it at the three levels of the generative path: fundamental, narrative and discursive. At the discursive level, the themes and ﬁgures of that alleged friendship were collected and their tensive and argumentative aspects were examined.